PENGARUH BOOK TAX DIFFERENCES DAN KEPEMILIKAN MANAJERIAL TERHADAP KUALITAS LABA DENGAN PERSISTENSI LABA SEBAGAI VARIABEL INTERVENING PADA PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BEI TAHUN 2016-2020 - Ramadhani, Izra Haflinda; Wiryaningtyas, Dwi Perwitasari; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
Earnings information in financial statements is an important focus in developing the company's ability or management accountability, for that companies need to pay attention to the quality of reported earnings so as not to mislead the users of the information. The purpose of this study was to analyze and test the effect of Book Tax Differences and Managerial Ownership on Earning Quality through Earning Persistence. This research is a quantitative research. The population in this study are all conventional banking companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Partial Least Square (PLS-SEM) Equation Model. The results of the direct influence test using the Smart PLS 3.0 application, show that the difference in Book taxes has a negative but not significant effect on Earnings persistence, Managerial ownership has a positive but not significant effect on Earnings persistence, Book tax differences have a negative but not significant effect on Earnings quality, Managerial ownership has an effect significantly positive on Earnings quality, Earnings persistence has a significant positive effect on Earnings quality. The results of the indirect effect hypothesis test show that the Book tax difference variable on Earnings quality through Earnings persistence has a negative but not significant effect, Managerial ownership on Earnings quality through Earnings persistence has a positive but not significant effect.